Peer Feedback Practices in Wiki Base Collaborative Writing: A Case Study in the EFL Saudi Context - Aljabri, Abdulaziz; Alshakhi, Abdullah (International Journal of English Language Education, 2024)
This study aimed to examine the perceptions and attitudes of EFL students regarding peer feedback practices in wiki-based collaborative writing tasks, as well as its impact on their writing performance. A total of 28 second-year high school students, who were studying English as a foreign language (EFL), participated in the study. Quantitative data was collected to answer the research questions. The key finding of this study indicates that the benefits of utilizing feedback practices for wiki-based writing outweigh the challenges they pose. Moreover, the majority of students hold positive attitudes towards exchanging feedback and engaging in wiki-based writing, which enhances their overall writing skills.